Investigations on power requirements for industrial compression strategies for carbon capture and sequestration - Nor Khonisah, Daud; Norhaslinda, Nasuha; Martynov, S.; Mahgerefteh, H. (IOP Publishing, 2019)
The main purpose of this study is to identify the optimum multistage compression strategies for minimising the compression and intercooler power requirements for pure CO2 stream. An analytical model based on thermodynamics principles is developed and applied to determine the power requirements for various compression strategies for pure CO2 stream. The compression options examined include conventional multistage integrally geared centrifugal compressors (option A), supersonic shockwave compressors (option B) and multistage compression combined with subcritical (option C) and supercritical liquefaction (option D) and pumping. In the case of determining the power demand for inter-stage cooling and liquefaction, a thermodynamic model based on Carnot refrigeration cycle is applied. From the previous study by [1], the power demand for inter-stage cooling duty was assumed to have been neglected. However, based on the present study, the inter-stage cooling duty is predicted to be significantly higher and contributes approximately 30% of the total power requirement for compression options A, C and D, while reaches 58% when applied to option B. It is also found that compression option C can offer higher efficiency than other compression strategies, while supercritical liquefaction efficiency is only marginally higher than that in the compression option A.